(untitled) (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2021)
Through GI i.e., geographical indication, an entrepreneur is able to differentiate his product/goods from other businessmen in the market. Meaning thereby, a GI is a mark which gives product significance on the basis of its originating region. For instance, Petha of Agra is famous, Rampuri Knife is also well known because of its place of origin.